A Model of Formative Assessment and Self Regulated Learning for Large Classes: An Interface between Internal and External Feedback - Jocson, Jennie V (ASPENSI in Bandung, Indonesia, 2012)
ABSTRACT: This paper presents how formative assessment can be used in large classes. In particular, this paper discusses the use of both internal and external feedback and how students may capitalize on using external feedback to help them process and take control of their own learning, making them self-regulated learners. A key argument this paper presents is that proper planning of assessment strategies in large classes provide avenues for students to use feedback from their teachers and their peers to guide their own feedback strategies in redesigning their works. Finally, a model of formative assessment angled at both external and internal feedbacks is proposed. The results proved that formative assessment is an important classroom tool in handling large classes. Particularly, in using formative assessment, the students take charge of their own learning, thus, giving their internal feedback which is critical in defining and redefining their works. Further, the results showed that timely feed-backing is necessary in order to achieve a well designed formative assessment plan. KEY WORD: Formative assessment, large classes, planning of assessment strategies, internal and external feedback, and self-regulated learners.Â IKHTISAR: Makalah ini menyajikan bagaimana penilaian formatif dapat digunakan di kelas-kelas besar. Khususnya, makalah ini membahas penggunaan umpan-balik internal dan eksternal dan bagaimana siswa dapat menggunakan umpan-balik eksternal untuk membantu mereka memproses dan mengontrol pembelajaran mereka sendiri, yang membuat mereka menjadi siswa yang mampu mengatur diri mereka sendiri. Alasan utama disajikannya makalah ini adalah bahwa perencanaan strategi penilaian yang tepat di kelas-kelas besar memberikan kesempatan bagi para siswa untuk menggunakan umpan-balik dari para guru dan teman-teman mereka untuk menuntun strategi umpan-balik mereka sendiri dalam merancang kembali pekerjaan mereka. Akhirnya, suatu model penilaian formatif berbelok pada umpan-balik internal dan eksternal yang disarankan. Khususnya, dalam menggunakan penilaian formatif, para siswa mempertanggungjawabkan pembelajaran mereka sendiri, sehingga memberikan umpan-balik internal yang penting dalam menjelaskan dan menentukan kembali pekerjaan mereka. Selanjutnya, hasil kajian menunjukan bahwa pemberian umpan-balik yang tepat merupakan hal yang sangat penting untuk mencapai suatu rencana penilaian formatif yang dirancang dengan baik. KATA KUNCI: Penilaian formatif, kelas besar, perencanaan starategi penilaian, umpan-balik internal dan eksternal, dan siswa yang mengatur sendiri.About the Author: Jennie V. Jocson, Ph.D. is a Lecturer at the Department of LBEL (Linguistics, Bilingual Education, and Literature), College of Languages, Linguistics, and Literature PNU (Philippine Normal University), Taft Avenue, Manila, Philippines. For academic purposes, she can be reached at: jeng_dana2@yahoo.com.ph and jocson.jv@pnu.edu.phHow to cite this article? Jocson, Jennie V. (2012). âA Model of Formative Assessment and Self Regulated Learning for Large Classes: An Interface between Internal and External Feedbackâ in SOSIOHUMANIKA: Jurnal Pendidikan Sains Sosial dan Kemanusiaan, Vol.5, No.2 [November], pp.227-238. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI, ISSN 1979-0112. Chronicle of article: Accepted (September 1, 2012); Revised (October 3, 2012); and Published (November 20, 2012). Â Â